2018
DOI: 10.1039/c8rp00052b
|View full text |Cite
|
Sign up to set email alerts
|

Using knowledge space theory to compare expected and real knowledge spaces in learning stoichiometry

Abstract: This paper proposes a novel application of knowledge space theory for identifying discrepancies between the knowledge structure that experts expect students to have and the real knowledge structure that students demonstrate on tests. The proposed approach combines two methods of constructing knowledge spaces. The expected knowledge space is constructed by analysing the problem-solving process, while the real knowledge space is identified by applying a data-analytic method. These two knowledge spaces are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Even though some of them tend to reduce the involvement of experts to some extent (e.g., the one that decomposes the problems in the sets of motives), all of them require a substantial amount of manual work. Another disadvantage of such methods, identified in [11] is that knowledge spaces that experts expect, often do not fit the test data properly so it was concluded that the real knowledge space often differs from the expected one. Theory-driven techniques are also inappropriate for constructing large knowledge spaces.…”
Section: Knowledge Space Constructionmentioning
confidence: 99%
“…Even though some of them tend to reduce the involvement of experts to some extent (e.g., the one that decomposes the problems in the sets of motives), all of them require a substantial amount of manual work. Another disadvantage of such methods, identified in [11] is that knowledge spaces that experts expect, often do not fit the test data properly so it was concluded that the real knowledge space often differs from the expected one. Theory-driven techniques are also inappropriate for constructing large knowledge spaces.…”
Section: Knowledge Space Constructionmentioning
confidence: 99%
“…In the literature, a variety of research methods have been conducted on the study of knowledge structure in science education. The methods include concept map (Adamov et al, 2009;Burrows & Mooring, 2015;Chiang et al, 2014), word association (Bahar & Tongac, 2009;Nakiboglu, 2008), phenomenological approach (Choi & Oh, 2021;Tóth & Ludányi, 2007), think-aloud interview (Ahmadian et al, 2019;King et al, 2022), multi-dimensional scaling (MDS) (Chiou & Anderson, 2010;Tilga et al, 2017), knowledge space theory (Segedinac et al, 2018), pathfinder network algorithm (Casas-Garcia & Luengo-Gonzalez, 2013), factor analysis , and reaction time technique .…”
Section: Knowledge Structure and Factor Analysismentioning
confidence: 99%
“…For the validation of this procedure, linear regression analysis was used, correlating student achievement and applied mental effort as dependent variables with the numerical rating of the cognitive complexity of the problem as an independent variable. In addition to the statistical procedure for validating the method for assessing the cognitive complexity of stoichiometric tasks, this method was further validated by applying Knowledge Space Theory (Segedinac, Horvat, Rodić, Rončević, & Savić, 2018). Knowledge Space Theory enabled the fine differentiation of concepts and the identification of differences between the expected knowledge space, which was constructed based on the numerical rating of cognitive complexity, and the real knowledge space, which was constructed based on the students' achievements.…”
Section: Examination Of the Effectiveness Of Instructional Strategiesmentioning
confidence: 99%